The Impact of the Recession on the Structure and Labour Market Success of Young NEET Individuals in Ireland - KELLY, ELISH MARY; MC GUINNESS, SEAMUS (ESRI, 2013)
The labour market consequences of the severe fall in economic activity that took place in Ireland after the recent global recession were quite stark, especially for young people. One particularly disquieting development has been the rise in the number of young people not in employment, education or training (NEET), which increased from 11.8 per cent in 2006 to 24 per cent in 2011 (Eurostat, 2013). Very little is known about NEET individuals in Ireland, either in terms of their profile or their labour market transitions, i.e., the extent to which youth NEETs have transitioned into employment. Given this information gap, and particularly its importance for the design of effective activation measures to assist young NEETs, this paper uses newly available longitudinal data from the Quarterly National Household Survey to examine the extent to which transitions to employment among NEETs and prime-aged unemployed changed over the recent recession in Ireland. The paper found that the rate of transition to employment fell dramatically for both groups between 2006 and 2011. The results from the analysis also revealed that the drop in the transition rates of NEET and prime-aged unemployed individuals? was not due to changes in the underlying sub-group population structures but to changes in external factors that have had an impact on individuals possessing certain characteristics during the recession. From a policy perspective, the results would seem to support a greater emphasis on higher levels of human capital (i.e., third-level qualifications) for young NEETs, and the redesign of vocational-type qualifications (i.e., Post Leaving Cert level courses) to increase their relevance to those areas of the labour market where jobs are emerging.
PUBLISHED
Keywords: Recession; Ireland; NEETS